(untitled) (Bangladesh Journal of Agricultural Research, 2016)
Identification of male fertility restorer genotypes for rapeseed CMS lines towards hybrid development in spring habit rapeseed (Brassica napus L.) adapted for short day winter season was studied. The experiment was conducted at the experimental farm and laboratory of Bangabandhu Sheikh Mujibur Rahman Agricultural University, Salna, Gazipur during October, 2008 to March, 2011. An exotic CMS-based F1 hybrid of rapeseed was selfed to get F2 generation with a view to resynthesizing restorer line. As a result a restorer line for Nap248A Z1 and Nap248A Z2 cytoplasmic male sterile lines was identified in the F3 generation of the exotic F1 rapeseed hybrid which appears as the first case so far reported as achievement in Bangladesh in this regard. Genetic analysis further revealed fertility restoration for Nap248A Z1 and Nap248A Z2 cytoplasmic male sterility was controlled by a single dominant nuclear gene as a simple genetic phenomenon. Bangladesh J. Agril. Res. 41(3): 529-540, September 2016